In vitro schistosomicidal activity of the lignan (−)-6, 6′-dinitrohinokinin (DNHK) loaded into poly(lactic-co-glycolic acid) nanoparticles against Schistosoma mansoni. (1st January 2017) - Lima, Thaís C.; Lucarini, Rodrigo; Luz, Priscilla P.; de Faria, Emerson H.; Marçal, Liziane; Magalhães, Lizandra G.; Badoco, Fernanda R.; Esperandim, Viviane R.; Molina, Eduardo F.; Laurentz, Rosangela S.; Lima, Regiane G.; Cunha, Wilson R.; et al.
Abstract: Context: (−)-6, 6′-Dinitrohinokinin (DNHK) display remarkable antiparasitic activity and was, therefore, incorporated into a nanoparticle formulation. Objective: Incorporation of DNHK in poly lactic-co-glycolic acid (PLGA) nanoparticles aiming to improve its biological activities. Materials and methods: Synthesis, characterization and incorporation of DNHK into glycolic acid (PLGA) nanoparticles by nanoprecipitation method. The nanoparticles were characterized by ultraviolet-visible spectroscopy, X-ray diffraction, field emission electron microscopic scanning mansoni (FESEM), and dynamic light scattering (DLS). For the in vitro test with Schistosoma mansoni, the DNHK-loaded PLGA was diluted into the medium, and added at concentrations 10–200 µM to the culture medium containing one adult worm pair. The parasites were kept for 120 h and monitored every 24 h to evaluate their general condition, including: pairing, alterations in motor activity and mortality. Results: The loaded PLGA nanoparticles gave an encapsulation efficiency of 42.2% and showed spherical characteristics in monodisperse polymeric matrix. The adult worm pairs were separated after 120 h of incubation for concentrations higher than 50 µM of DNHK-loaded PLGA. The groups incubated with 150 and 200 µM of DNHK-loaded PLGA for 24 and 120 h killed 100% of adult worms, afforded LC50 values of 137.0 ± 2.12 µM and 79.01 ± 1.90 µM, respectively, which was similar to the effect displayed by 10 µM of praziquantel. Discussion and conclusions: The incorporation of DNHK-loaded showed schistosomicidal activity and allowed its sustained release. The loaded PLGA system can be administered intravenously, as well as it may be internalized by endocytosis by the target organisms.